Critical Synthesis Package: Global Simulated Patient Rating Scale - Jeremy Richards (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Global Simulated Patient Scale (GSPRS), and (2) a copy of the GSPRS instrument developed by Gerald Michael Humphris. The GSPRS is a simple, one item ranking scale designed to be used by simulated patients to assess medical students' communication skills in an OSCE. There are a few studies describing the GSPRS's reliability and validity, and those found primarily document its use with first- and second-year medical students in England in the late 1990s. In these studies, the GSPRS demonstrated only acceptable reliability as demonstrated by generalizability studies. Decision studies indicate that increasing the number of ratings may improve the GSPRS's reliability. Validity has been described with regard to examiner consistency, and it was determined that no significant differences in ratings at the beginning versus the end of an OSCE were noted. Furthermore, construct validity is reflected in an increase in GSPRS ratings in students progressing from their first- to their second-year of medical school. Potential issues with the GSPRS include the fact that variability in training patients could have substantive effects on reliability and validity of this tool, the psychometric characteristics were derived from cohorts of students in the late 1990s in England, and the relationship between GSPRS and other metrics of students' knowledge, skills, and attitudes has not been well-described. However, the GSPRS provides a distinct, adequately reliable, and potentially valid data point with regard to students' communication skills. Considering relevancy of the published characterizations of the GSPRS's psychometric properties, if educators choose to use this tool, it should be combined with other assessments and not used as a stand-alone measure of students' communication skills.